Perceptions of Support Among Older African American Cancer Survivors - Hamilton, Jill B. (2010)
PURPOSE/OBJECTIVES: To explore the perceived social support needs among older adult African American cancer survivors. RESEARCH APPROACH: Qualitative design using grounded theory techniques. SETTING: Outpatient oncology clinics in the southeastern United States. PARTICIPANTS: Focus groups with 22 older adult African American cancer survivors. METHODOLOGIC APPROACH: Purposeful sampling technique was used to identify focus group participants. In-depth interviews were conducted and participants were interviewed until informational redundancy was achieved. MAIN RESEARCH VARIABLES: Social support needs of older adult African American patients with cancer. FINDINGS: Social support was influenced by (a) symptoms and treatment side effects, (b) perceptions of stigma and fears expressed by family and friends, (c) cultural beliefs about cancer, and (d) desires to lessen any burden or disruption to the lives of family and friends. Survivors navigated within and outside of their networks to get their social support needs met. In some instances, survivors socially withdrew from traditional sources of support for fear of being ostracized. Survivors also described feeling hurt, alone, and socially isolated when completely abandoned by friends. CONCLUSIONS: The support from family, friends, and fellow church members is important to positive outcomes among older African American cancer survivors. However, misconceptions, fears, and negative cultural beliefs persist within the African American community and negatively influence the social support available to this population. INTERPRETATIONS: Early identification of the factors that influence social support can facilitate strategies to improve outcomes and decrease health disparities among this population.